Kontribusi Perbankan Syariah Dalam Mendukung Terciptanya Green Finance Di Indonesia - Avivah, Iin Nur; Muharrami, Rais Sani (EKSISBANK (Ekonomi Syariah dan Bisnis Perbankan), 2023)
Environmental pollution, air pollution and other related problems related to environmental pollution are economic problems. Therefore, policymakers require that economic development must truly implement a green vision in the new era. The proactive role of sharia banking is needed to support the creation of green finance as a lender that will stimulate industry to implement environmental management in concert to sharia maqosid. This research aims to provide a valuable contribution to the existing literature regarding sustainable sharia banking and green finance in the context of sharia banking. By using a qualitative and descriptive approach, this research aims to present an in-depth understanding of sharia banking practices that focus on sustainability and their impact on green finance through library research techniques by exploring the sustainability reports of 8 sharia banking institutions that consistently issue reports, namely : Bank Muamalat, Bank Mega Syariah, Bank Bukopin Syariah, Bank Victoria Syariah, BCA Syariah, BJB Syariah, BTPN Syariah and BSI in the 2020-2022 period. During 2020 – 2022. This research has the results that 8 Sharia Banking in Indonesia are committed to supporting sustainability through sustainable financing and participation in environmental initiatives. Some banks experienced fluctuations in financial performance, while others recorded significant increases in sustainable financing.